Empowerment of human resources as a step towards administrative reform - Miri, Karima (Social Empowerment Journal, 2021)
Through this article, we shed light on the principle of management democracy by addressing the issue of administrative empowerment of human resources as a contemporary management trend concerned with the participation of a strong leader authority with his subordinates, and the dissemination of team spirit.